Marine baseline and monitoring strategies for carbon dioxide capture and storage (CCS). (July 2015) - Blackford, Jerry; Bull, Jonathan M.; Cevatoglu, Melis; Connelly, Douglas; Hauton, Chris; James, Rachael H.; Lichtschlag, Anna; Stahl, Henrik; Widdicombe, Steve; Wright, Ian C.
Highlights: Development of a marine monitoring system suitable for operational CCS is achievable. Monitoring should be hierarchical, starting with anomaly detection. Comprehensive baselines are required to support monitoring. Abstract: The QICS controlled release experiment demonstrates that leaks of carbon dioxide (CO2 ) gas can be detected by monitoring acoustic, geochemical and biological parameters within a given marine system. However the natural complexity and variability of marine system responses to (artificial) leakage strongly suggests that there are no absolute indicators of leakage or impact that can unequivocally and universally be used for all potential future storage sites. We suggest a multivariate, hierarchical approach to monitoring, escalating from anomaly detection to attribution, quantification and then impact assessment, as required. Given the spatial heterogeneity of many marine ecosystems it is essential that environmental monitoring programmes are supported by a temporally (tidal, seasonal and annual) and spatially resolved baseline of data from which changes can be accurately identified. In this paper we outline and discuss the options for monitoring methodologies and identify the components of an appropriate baseline survey.